2022
DOI: 10.3389/fgene.2021.817672
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Mitochondrial-Associated Protein LRPPRC is Related With Poor Prognosis Potentially and Exerts as an Oncogene Via Maintaining Mitochondrial Function in Pancreatic Cancer

Abstract: Background: The mitochondrial-associated protein leucine-rich pentatricopeptide repeat-containing (LRPPRC) exerts multiple functions involved in physiological processes, including mitochondrial gene translation, cell cycle progression, and tumorigenesis. Previously, LRPPRC was reported to regulate mitophagy by interacting with Bcl-2 and Beclin-1 and thus modifying the activation of PI3KCIII and autophagy. Considering that LRPPRC was found to be negatively associated with survival rate, we hypothesize that LRPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Its expression is signi cantly higher than that in adjacent tissues, and LRPPRC negatively correlates with overall survival [14]. Knockdown of LRPPRC inhibited the malignant biological behavior of PANC-1 cells, including proliferation and migration [15]. We also show that WTAP plays an essential role in many physiological processes in the cell, including binding to the 3 ′ untranslated region of the mRNA to improve mRNA stability [16].…”
Section: Discussionmentioning
confidence: 86%
“…Its expression is signi cantly higher than that in adjacent tissues, and LRPPRC negatively correlates with overall survival [14]. Knockdown of LRPPRC inhibited the malignant biological behavior of PANC-1 cells, including proliferation and migration [15]. We also show that WTAP plays an essential role in many physiological processes in the cell, including binding to the 3 ′ untranslated region of the mRNA to improve mRNA stability [16].…”
Section: Discussionmentioning
confidence: 86%
“…It is reported that GAA acts as an anti-tumor agent, via targeting to LRPPRC and resulted in protein degradation[ 16 ], we treated KG1a-SCs and Kasumi-1-SCs with GAA with different concentrations ranged from 2.5-10 μmol/L for 24 h. By performing western blot, it is presented that 5-10 μmol/L GAA treatment significantly decreased LRPPRC protein levels after 24 h via promoting protein degradation (Figure 1B ), without affecting LRPPRC transcription (data not shown). By considering that LRPPRC acts as a oncogenic factor in several kinds of cancer[ 18 , 19 ], we then evaluate the effect of GAA on KG1a-SCs and Kasumi-1-SCs cell viability and colony formation. As shown in Figure 1C , GAA treatment ranged from 5-10 μmol/L significantly decreased cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…For chemoresistance, previous studies suggested that the impaired mitophagy restricted the metabolic plasticity, which made the pancreatic cancer cells susceptible to metformin treatment (40). However, another related research showed that mitophagy could inhibit malignant behaviors including chemoresistance in pancreatic cancer cells (41). Therefore, there remain many controversies between mitophagy and chemoresistance in pancreatic cancer, which deserves further study (42).…”
Section: Discussionmentioning
confidence: 99%